A Novel Framework for Information Hiding and Image Encryption using Least Significant Bit Techniques - Kekre, H. B.; Sarode, Tanuja; Halarnkar, Pallavi (European Journal of Applied Sciences, 2014)
Security of Digital Images is utmost important. Nowadays not only data but also digital images are increasing in a huge number. Good encryption techniques are always in need. In this paper we have proposed a Novel Framework, which is a combination of Information Hiding and Image Scrambling. The proposed framework is one of its kind and doesn’t resemble to any existing frameworks in literature. For Image scrambling R-Prime Shuffle technique has been used.